Exploring the Level of Self-Care Behavior, Motivation, and Self-Efficacy among Individuals With Hypertension: A Cross-Sectional Study - Salam Bani Hani PhD, RN; Mohammad A. Abu Sabra PhD, PMHN-CNS; Marwa Nayef Alhalabi PhD; Ahmad Emad Alomari MD; Emran A. Abu Aqoulah PhD, MSc, RN (SAGE Publishing, 2024)
Introduction Hypertension is a serious public health issue. It is a significant but controllable factor in the emergence of cardiovascular disease. Controlling hypertension is a main target for individuals to prevent further illness. Objective This study aims to explore the level of self-care behaviors, motivation, and self-efficacy among individuals with hypertension. Methods A cross-sectional, descriptive, correlational design was used to recruit ( n  = 121) participants utilizing the Hypertension Self-Care Profile (HTN-SCP) questionnaire. Results The analysis revealed that the mean score of self-care behavior was 49.7 ( SD  = 10.0) out of 20-80, which indicates that they are likely to have good self-care behavior. The mean score of motivation for self-care was 59.7 ( SD  = 11.8) out of 20-80, reflecting that individuals with hypertension have a good level of motivation for self-care, and the mean score of self-efficacy was 70.0 ( SD  = 9.8) out of 20-80, which means that individuals with hypertension have a high level of self-efficacy. Also, there was a significant positive correlation between self-care behavior and motivation for self-care ( r  = .527, p  < .001), between motivation for self-care and self-efficacy ( r  = .554, p  < .001), and between self-efficacy and self-care behavior ( r  = .572, p  < .001). Conclusion The study revealed that Jordanian patients with hypertension have good self-care practices, motivation, and high self-efficacy. Patients should therefore be strongly recommended to be compliant with self-care practices. The government should prioritize hypertensive patients by making it easier for them to receive information about self-management practices to improve their quality of care.